2022
DOI: 10.2478/aoas-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

Carcass and Meat Quality of Lambs from Thin-Tailed and Fat-Tailed Breeds at Five Different Slaughter Weights

Abstract: In lamb production, deciding the optimal slaughter weight (SW) has great importance on product quality. Aim of the study was to determine the optimum SW for lambs from a thin-tailed breed (Kivircik) and a fat-tailed breed (Kangal Akkaraman) in order to get high-quality meat and carcass. Kivircik (n=60) and Kangal Akkaraman (n=59) lambs were allotted to five SW groups (20, 28, 36, 44 and 52 kg). In Kivircik lambs, backfat thickness and fatness score gradually increased in parallel with the increase in SW, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Among the meat quality characteristics, a significant birth type effect was detected for only for the express juice, which might be a result of the single lambs having higher slaughter weights. Both Vergara et al [52] and Ekiz et al [53] found an increase in the express juice of lambs with higher slaughter weights, which was related to lower carcass fatness, similar to our findings with single born lambs. However, this situation was reported as breed and/or weight-class specific in some cases [54].…”
Section: Discussionsupporting
confidence: 91%
“…Among the meat quality characteristics, a significant birth type effect was detected for only for the express juice, which might be a result of the single lambs having higher slaughter weights. Both Vergara et al [52] and Ekiz et al [53] found an increase in the express juice of lambs with higher slaughter weights, which was related to lower carcass fatness, similar to our findings with single born lambs. However, this situation was reported as breed and/or weight-class specific in some cases [54].…”
Section: Discussionsupporting
confidence: 91%
“…The results of our study mainly show that the LWS had a significant effect only on a*, while the higher the LWS, the redder the meat. Ekiz et al (2022) also reported a significant increase of meat redness with the increasing LWS. However, the authors further noted a significant decrease in the lightness of meat.…”
Section: The Effect Of Lws On Chemical and Physical Characteristics O...mentioning
confidence: 87%